Pediatric Acute Hematogenous Osteomyelitis. Issue 6 (September 2015) - Street, Matthew; Puna, Rupesh; Huang, Mark; Crawford, Haemish
<x xml:space="preserve">Abstract</x> Background: Osteomyelitis continues to be a significant problem among the New Zealand pediatric population. We present a large series of acute hematogenous osteomyelitis (AHO) cases, with the aim to identify any changing trends and guide successful management of the disease. Methods: A 10-year retrospective review was performed of clinical records of children with AHO at the 2 children's orthopaedic departments in the Auckland region. Cases were identified from Starship Children's Hospital between 1997 and 2007 and Middlemore's Kidz First Hospital between 1998 and 2008. Results: A total of 813 cases of pediatric AHO were identified. The incidence was 1:4000, which was decreasing over the 10-year period. There was a male predominance and New Zealand (NZ) Maori and Pacific Islanders were overrepresented. The diagnosis was made clinically in 27%, radiographically in 66%, and surgically in 7%. The most common pathogen was Staphylococcus aureus and the incidence of methicillin-resistant S. aureus was low (2%). The average length of antibiotic treatment was 44 days and 44% required surgery. This produced a recurrence rate of only 7% and a 15% treatment-related complication rate. Conclusions: In the New Zealand population, the incidence of AHO remains high with NZ Maori and Pacific Islanders overrepresented. The predominant pathogen remains S. aureus and our population has a very low incidence of methicillin-resistant S. aureus; flucloxacillin remains a good choice for empiric treatment in our population. Our rate of relapse and subsequent chronic osteomyelitis is low. This could be explained by traditionally longer antibiotic courses; however, this may also lead to increased treatment-related complications. Through prompt and accurate diagnosis with the aid of laboratory and radiologic tests and effective treatment with appropriate antibiotics (guided by local pathogen sensitivities) and surgical treatment when indicated, AHO can be well managed with minimal severe complications. Level of Evidence: Level IV—retrospective case series.